Using Prospecting to Expand Your Customer Base - Kara DiNardo; Allen F. Wysocki (EDIS)
This document is intended for salespeople who must seek out potential customers by prospecting, as opposed to waiting for potential customers to enter a retail establishment. Obtaining a customer base from which sales can be achieved is one of the most challenging aspects of selling, especially for a new salesperson. Prospecting involves contacting potential customers for the purpose of creating new sales for the salesperson. Prospecting is as old as the profession of selling and has always been an important method of obtaining new customers. However, while prospecting is a good way to increase sales, it is also one of the most difficult. One reason why prospecting is often avoided is its high failure rate; it is a struggle to be motivated to prospect when it seems to be met with constant failure. This paper will focus on three keys to successful prospecting: overcoming barriers to prospecting, making effective use of prospecting time, and creating interest. This is EDIS document SN012, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published May 2003.